Antibiotic Susceptibility Testing. Issue 10 (October 2015) - Arena, Fabio; Viaggi, Bruno; Galli, Luisa; Rossolini, Gian Maria
<x xml:space="preserve">Abstract</x> Supplemental Digital Content is available in the text.